Diagnosis of supra-aortic artery stenosis: comparison of magnetic resonance angiography imaging methods with conventional digital subtraction angiography - Aydin, Hale; Muhtesem, Agildere A. (International Journal of Research in Medical Sciences, 2018)
Background: The aim of this study was to compare conventional digital subtraction angiography (DSA) with the multi-planar reformation (MPR) and maximum intensity projection (MIP) reconstruction of servical magnetic resonance angiography (MRA) in terms of detecting supra-aortic artery stenoses. Methods: In the study, 21 patients who had underwent 3D MRA and conventional DSA were retrospectively assessed. Axial MPR, coronal MIP reconstruction and contrast enhanced 3D MRA subtraction images of a total of 333 artery segments were independently assessed by 2 separate radiologists. Conventional DSA results were accepted as gold standard results. The overall and individual Kappa values of all methods were calculated. Results: Results of the conventional DSA analysis indicated total occlusion in 9 (2.7%), severe stenosis in 16 (4.8%), moderate stenosis in 90 (27.1%), mild stenosis in 105 (31.5%) and no stenosis in 113 (33.9%) arteries. While the k values of all methods were high which demonstrated strong relationships with the DSA method; the coronal MIP reconstruction method was found to be superior to other methods. The 3D MRA subtraction method did not yield better results in any of the individual comparisons. Conclusions: Our results indicate that the coronal MIP reconstruction method has higher correlation with conventional DSA results compared to the other two methods and may be used as an accurate first-line diagnostic method for supra-aortic artery stenoses.